Perception of Attributes of Organic and Conventional Farming by Farmers in Andhra Pradesh - B. Savitha,; R. Ratnakar,; K. Suhasini, (Journal of Agricultural Extension Management, 2025)
This study was conducted in three districts of Andhra Pradesh namely Warangal, Chittoor and East Godavari in the year 2009, to study the perception of attributes of organic and conventional farming by the respondent farmers. The findings of the study indicate that majority of the organic farmers perceived the initial cost, net profitability and consistency of profits of organic farming as high, it is a time taking process but derives multiple benefits. When compatibility of organic farming was studied it was found that, it is situationally, culturally and relationally compatible and is having cognitive, application and resource complexity. Further, it was also observed that majority of the organic farmers felt it as practicable, sustainable, results of organic farming as certain but not observable and as having low perceived risk. The conventional farmers perceived their farming as costly, net profitability and consistency of profits as irregular, a time taking process and. deriving single benefit. In case of compatibility it was found that, conventional farmers felt it as situationally, culturally compatible and relationally independent and not having cognitive application and resource complexity. Further, it was also observed that majority of the conventional farmers perceived it as practicable, unsustainable, with uncertain results and high perceived risk